ANALISIS EFEKTIVITAS PENGELOLAAN DANA PROGRAM “BANTU UMAK” DALAM MENURUNKAN TINGKAT KEMISKINAN (STUDI KASUS PADA DINAS SOSIAL KABUPATEN MUSI BANYUASIN) - Ahmad Irfansyah (Jurnal Ilmiah Akuntansi Rahmaniyah, 2026)
This study aims to analyze the management of funds for the Bantu Umak Program at the Musi Banyuasin Regency Social Services Office, examining the aspects of planning, implementation, monitoring, and evaluation. It also analyzes the effectiveness of program fund management in reducing poverty based on indicators of targeting accuracy, timeliness, amount accuracy, procedural accuracy, and program sustainability. The results indicate that the management of Bantu Umak Program funds has been carried out through the planning, implementation, monitoring, and evaluation stages in accordance with applicable regulations. Planning is carried out through data collection and verification of prospective beneficiaries. Program implementation is carried out in collaboration with Bank Rakyat Indonesia as the aid distributor, while monitoring and evaluation are conducted periodically by the Social Services Office and related parties. Based on effectiveness indicators, the Bantu Umak Program is considered quite effective because it has met most of the indicators, namely targeting accuracy, amount accuracy, procedural accuracy, and program sustainability. However, obstacles remain in the form of delays in aid distribution due to limited regional financial capacity.